Is There Something of Divinity Regarding R. M. Hare’s Account of Reason? - Xinyu Wang; Yingping Wu (Religions, 2025)
This article delves deeply into the moral rationalism advocated by R. M. Hare. Traditionally, the ultimate normativity of morality has been attributed to divine characteristics such as the abstract concepts of universality, transcendence, necessity, and ultimate authority, but Hare explicitly rejects any theological premises and seeks to base moral obligations on a pure structure of linguistic and rational consistency. However, this paper proposes that Hare’s secular rational system inevitably reproduces the functional structure of the divine moral order at its internal logical level. To demonstrate this, the key conceptual attributes involved in “divine normativity” are separated first, and an analytical framework is constructed. At the same time, this paper analyzes how the normative requirements, such as universality and prescriptiveness in the Hare system, relate to the attributes of divine norms. The results show that although Hare appears to maintain thorough secularism on the surface, the moral rationalism emphasis on consistency and universal applicability functionally reproduces a normative structure similar to divine commands. This finding reveals a profound philosophical paradox: even stripped of metaphysical assumptions, human attempts to pursue an objective moral order still tend to appeal to transcendent structures in an implicit way. This paper offers a critical examination of Hare’s theory, affirming both his ambition in the construction of secular moral thought and revealing the underlying tension within it that cannot completely break away from the framework of theological tradition.